Dictionaries as pedagogic tools: a case study of selected schools in Makhanda, Eastern Cape - Wababa, Zola Richman (Rhodes University, Faculty of Humanities, School of Languages and Literatures)
The importance of dictionaries in society has been confirmed in relevant literature while their specific role in education is underlined by several studies focused on the use of dictionaries in teaching and learning. This study focuses on mother-tongue or first language (L1) isiXhosa learners and their use of dictionaries across subjects in the Intermediate Phase of primary schooling. The research sought to examine how dictionaries are used in teaching and learning and how they could be used more effectively in the teaching and learning processes, with a focus on isiXhosa L1 learners in the Makhanda area of the Sarah Baartman District of education, Eastern Cape. The general aim of this study was to improve the process and practice of using and producing Language for General Purpose (LGP) and Language for Specific Purpose (LSP) dictionaries across subjects. The study also sought to contribute to improving the functional value and user-friendliness of teaching support materials, such as dictionaries. The Curriculum and Assessment Policy Statement (CAPS) policy document states that dictionaries are essential in teaching and learning of both language and content subjects. In relation to language subjects, the CAPS is explicit about the use of dictionaries in the acquisition of vocabulary, meaning, spelling, pronunciation, and grammar, among other types of information that are integral in language attainment and learning. Nonetheless, the CAPS document does not clearly articulate the use of dictionaries in content subjects. The study draws on two branches of lexicography "“ namely, dictionary user research and dictionary criticism "“ to examine the extent to which dictionaries are problem-solving tools which assist users to meet their cognitive and communicative needs. Thus, the study seeks to influence policy and practice of the use of dictionaries as teaching and learning resource materials that could help teachers and learners better understand key concepts across subjects. A mixed-method approach was used to collect both quantitative and qualitative data using a variety of data collection instruments, viz., observation schedules, questionnaires, and interviews. The study found that although teachers were aware of dictionaries, they did not use them as a resource in teaching. Furthermore, teachers lacked skills in the use of dictionaries, therefore, they were not able to effectively integrate dictionaries in their lessons. The research also found that learners had little awareness of dictionaries and did not fully understand their role in language acquisition or content. Lastly, the study offered some insights on how dictionaries could be integrated in teaching and learning, and how their use could address some communicative and cognitive problems faced by non-mother tongue English speakers in a context where English dominates teaching and learning at the expense of learners' L1.
Keywords: Encyclopedias and dictionaries -- History and criticism; Teaching; Sublanguage -- Dictionary; Lexicography; English language -- Control